TRANSFORMATION OF THE CULTURAL LANDSCAPES OF UKRAINIAN CITIES IN THE REAR IN THE CONTEXT OF THE FULL-SCALE WAR - Stepanenko, Anastasiia (Ukrainian Cultural Studies, 2023)
The War between the Russian Federation and Ukraine is one of the most devastating conflicts in history, with an unprecedented scale in Europe since World War II. It has a profound impact on Ukrainian society, resulting in complex changes on multiple levels, including economic, political, cultural, and social aspects. The cultural landscape of Kyiv undergoes transformations of varying intensity and nature throughout the year 2022. These processes can be caused by changes in the functions of sociocultural institutions and architectural structures, alterations in the names of urban toponyms, the placement of military posts, and defensive structures, as well as shifts in the perception of public space and associations related to the city. It has a significant impact on the identity of the city and its residents, as well as on the perception of events and public activism. Creative communities, artistic associations, and cultural and artistic-oriented civic organizations that continue their activities have adapted their work and become part of an active volunteer movement. This article aims to explore the comprehensive effects of the war on the general trends of cultural landscape transformation in Ukrainian cities. It examines various aspects of how the war has influenced Kyiv, such as its impact on the creative sector, changes in media hierarchy, the transformation of urban cultural practices, and changes in the supply and demand of cultural products and services at the local level. The article attempts to investigate and systematize the processes of cultural landscape transformation in Ukrainian cities that have not been directly involved in active combat during the ongoing war of Russia against Ukraine. By adopting a comprehensive approach, this research seeks to encompass various facets of the war’s influence on cities and urban communities and facilitate an understanding of their interconnectedness with the broader trends of cultural landscape transformation